Toleransi Meja Makan: Bisnis, Budaya Pedagang Kuliner, dan Interaksi Sosial Pedagang di Kota Singkawang - Sri Sudono Saliro; Tamrin Muchsin; Baharuddin Baharuddin (NALAR, 2021)
This study attempted to analyze the relationship between  tolerance values amongst religious followers with culinary trade culture in running a business, which was a hereditary cultural heritage. The interaction activities of culinary traders in Singkawang City were very unique, such as "pekong porridge" traders selling the products in the Secretariat of the Indonesian Taoist Council of Singkawang City. The study focused on bussiness patterns in culinary trade culture and its implication toward the tolerance amongst religious followers and ethnic society. This study is a qualitative. The data were gathered through observation and interviews. This finding revealed that dining table tolerance in Singkawang City was formed through trade culture diplomacy. In addition, trade culture and culinary consumption culture in traditional areas and Hong Kong markets made a bridge dialogue, social interaction, and social harmonization between ethnicities and religions at Singkawang City. Therefore, it was concluded that culinary did not only represent the identity of a society but also became the right medium to establish harmony between ethnic and religious societies. In the context of culinary traders at Singkawang City, tolerance built on the dining table was a community culture to eat together, which was then interspersed with dialogue and interaction, which indirectly had implications for fostering an attitude of tolerance between religions and ethnicities in a plural society center.Keywords: Tolerance; Trade Culture; Culinary Culture; Singkawang